Work as an educational principle and overcoming the Brazilian educational duality (Research, Society and Development, 2019)
The present work is a preliminary study about the Education and its transformations throughout history. We intend to address the division suffered by the education with the private property’s arrival, highlighting its ramifications in the current brazilian educational program. In this article, we aim to understand the dichotomy expressed in the different education projects currently present in Brazil.   We also intend to reflect on a perspective of overcoming this dual model through an educational praxis that takes work as an educational principle. We’ll analyze the Work’s role as a educational principle and its relation with the Education’s genesis, understanding that its resumption points to a possible horizon for overcoming the current duality expressed in a education for the working class and one for the dominant class. It is understood that Work is a founding category of the social being. The tour is based on the thinking of Marxian field theorists who reflect on an education for human emancipation.